Pencegahan Kekerasan Dalam Rumah Tangga Terhadap Perempuan Dan Anak di Desa Mojorejo - Sari Rahayu; Hilmi Jauhar; Fachry Lazuardy; Nur Mochamad; Rachmatus Ananda; Hany Pratondo; Apriliana Priska; Romadhoni Dika; Arnold Gabriel; Paulanda Putri; Yulita Alfiana; Riyanto Riyanto; Kurnia Renita; Sistyaningsih Retno; Tya Yania; Arya Galuh; Riko Mochammad; Duwy Putry; Khoirudin Khoirudin; Nadya Agnes; Aditya Rivan; Shukri Muhamad; Arifin Arifin (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The service's goal is to promote public understanding of domestic violence prevention and build awareness among the inhabitants of Mojorejo Village. Counseling activities in the community are motivated by phenomena that occur in the community. The problem of domestic violence itself is actually a problem that often occurs in married life, but some people do not consider what they experience as an act that is wrong in the eyes of the law. Therefore, the community needs to be given an understanding of domestic violence, so that if it occurs or experiences domestic violence, the victim can take legal steps. The method used is a participatory method which is expected to play an active role in legal counseling activities in the form of; Lecture on the Socialization of Law Number 23 of 2004 concerning Domestic Violence; Legal counseling regarding the material of Law Number 23 of 2004 concerning Domestic Violence; Question and answer session about domestic violence through mediation.